P-648 Intramuscular progesterone as a rescue therapy for optmized luteal phase support in patients with low progesterone levels during elective euploid single embryo transfer. (30th June 2022) - Roque, M; Da Rosa Filho, R; Hatty, J.H; Portela, R; Cecchino, G.N
Abstract: Study question: Does the addition of intramuscular progesterone(P) may improve the clinical outcomes of FET cycles in cases of low serum P levels before embryo transfer? Summary answer: Intramuscularly P may correct the potentially harmful effects associated with low serum P levels during the luteal phase in FET cycles performed under HRT. What is known already: Compelling evidence suggests that during FET, P levels measured on the mid-luteal phase may impact pregnancy outcomes, indicating that regardless of uterine P levels, a minimum level of serum P is required to enhance clinical outcomes. Up to one-third of patients under HRT using intravaginal micronized progesterone during FET cycles may present inadequate serum P levels, which may decrease the live birth rate in up to 32% when compared to patients with adequate serum P levels. Thus, the individualization of the LPS according to P monitoring may be necessary to overcome the deleterious effect of low P levels before FET. Study design, size, duration: A retrospective cohort study was conducted between August 2019 and June 2021. Patients undergoing elective single embryo transfer (eSET) of euploid day 5 or day 6 blastocysts with own oocytes were included in the study. During the study period, 305 patients fulfilled the inclusion criteria. Participants/materials, setting, methods: In patients presenting with serum P levels <9.2 ng/mL on the day before the ET, 1 mg/day of intramuscular P was added as a rescue therapy on the day of the ET and was maintained until the blood pregnancy test was completed; this represented the rescue LPS (rLPS) group. The clinical outcomes of rLPS group were compared to those patients with adequate serum P levels that maintained the LPS with vaginal micronized P (tLPS group). Main results and the role of chance: During the study period, 305 patients fulfilled the inclusion criteria. There were 198 patients (65%) with adequate serum P levels that maintained the LPS with vaginal micronized and oral P (tLPS group), while 107 patients (35%) presented with low P levels in which a rescue intramuscularly administered P was added on the day of the embryo transfer (rLPS). When comparing the groups, there was no statistical difference in terms of maternal age, BMI, endometrial thickness before starting the P administration, estradiol and P levels in the proliferative phase, E levels in the luteal phase. There was a statistically significant difference in P levels on the day before the embryo transfer when comparing the tLPS and rLPS groups (13.6±6.2 ng/mL and 7.5±1.9 ng/mL, respectively; P <0.0001). No significant difference was observed in the clinical outcomes when comparing the tLPS and rLPS. The pregnancy rates were 73.7% and 72.0% (aOR=0.91, 95% CI 0.54–1.55; P =0.74), clinical pregnancy rates were 69.2% and 68.2% (aOR=0.96, 95% CI 0.58–1.55; P =0.86), and ongoing pregnancy rates were 65.7% and 64.5% (aOR=0.95, 95% CI 0.58–1.55; P =0.84) in the tLPS and rLPS respectively. The multivariate logistic regression did not identify any independent factor related to the ongoing pregnancy rate. Limitations, reasons for caution: A control group comprising patients with low P levels that did not receive any intervention is lacking. However, we believe it would be unethical to neglect evidence from previous studies suggesting that low P levels might reduce reproductive outcomes in this group of patients. Wider implications of the findings: Although previous clinical studies concluded that low luteal P levels before FET might impact clinical outcomes, we observed that intramuscular P administration starting on the day of euploid blastocyst ET, as a novel rescue therapy, can lead to comparable results to those achieved in patients presenting with adequate P levels. Trial registration number: -